Peningkatan Kemampuan Menulis Puisi dengan Model Pembelajaran Telisik (Tentukan, Analisis, Tampilkan) - Wicaksono, Helmi; Tabrani, Akhmad (Attractive : Innovative Education Journal, 2020)
The aim of this article was to improve the ability in writing poetry through model of Telisik (Tentukan, Analisis, Tampilkan). The research method was Classroom Action Research (CAR) which consisted of four stages, namely 1) planning, 2) implementation, 3) observation and 4) reflection. The subjects in this study were 18 first semester students of language and literature study program at Universitas Islam Malang. This research was conducted during two actions (cycles). Data collection techniques was interviews, questionnaires, observation and test results. From the results of the study showed that there was increasingthe ability to write poetry with the Telisik model. Student mastery learning increased from 39% up to 66%. The implementation of the second cycle showed success. A significant increase was also seen from the results of the second cycle. The level of completeness of students reached 88%. Learning model of Telisik (Tentukan, Analisis, Tampilkan) which is supported by effective media and teacher attention, was an important factor supporting the success of learning activities. Keywords: Telisik (Tentukan, Analisis, Tampilkan), Learning Model, Increasing Writing Poetry